Pan-immune-inf lammation value and systemic immune-inf lammation index predict the clinical efficacy of biological agents in Crohn’s disease - Bin Liu; Daoli Liu; Chongbin Qi; Caroline Sunggip (Oxford University Press, 2025)
Background It remains unclear whether pan-immune-inflammation value (PIV) and systemic immune-inflammation index (SII) can predict treatment outcomes in Crohn’s disease (CD) patients receiving infliximab. This study explored the role of PIV and SII in predicting treatment response and prognosis in CD patients receiving biologics. Methods Clinical data of 160 patients with CD were retrospectively collected from Anqing First People’s Hospital in China. Patients were classified into effective and ineffective groups based on therapeutic response. Additionally, 60 healthy controls were enrolled. Serum levels of PIV and SII were measured in all participants. The effectiveness of infliximab was evaluated based on Crohn’s Disease Activity Index. Clinical remission was defined as a Crohn’s Disease Activity Index score <150, while a reduction of ≥70 points from baseline indicated clinical response. Results The effective group included 125 patients (mean age, 34.5 ± 10.2 years; 68 men [54.4%]), and the ineffective group included 35 patients (mean age, 36.1 ± 9.8 years; 18 men [51.4%]). The healthy control group covered 60 individuals (mean age, 33.8 ± 11.1 years; 32 men [53.3%]). Patients in the high SII group demonstrated a markedly elevated hazard ratio (HR = 20.786, P < .001). A higher PIV was associated with better prognosis (HR = 0.386, 95% confidence interval: 0.228–1.655, P = .011). Conversely, a higher SII was associated with worse prognosis (HR = 20.786, 95% confidence interval: 9.412–45.902, P < .001). Conclusions Both PIV and the SII are useful in predicting efficacy of CD patients treated with biologics. Compared with SII, PIV is a better choice. Key messages What is already known on this topic: Infliximab is the most efficacious and widely used biologic for inducing remission in moderate-to-severe Crohn’s disease. SII and PIV have been validated as prognostic indicators in many diseases. What this study adds: Higher PIV and SII both have positive effects on predicting the prognosis of patients with Crohn’s disease. Compared with the SII, the PIV holds greater significance in predicting the clinical outcomes for patients with Crohn’s disease. How this study might affect research, practice or policy: PIV and SII may aid in risk stratification and individualized treatment planning in Crohn’s disease.